ANALISIS TIPOGRAFI PADA JUDUL FILM ANIMASI DISNEY GENRE PETUALANGAN TAHUN 2019 – 2021 - Naura Annisa Iskandar; Riama Maslan Sihombing (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2022)
Typography has become a very important thing in the world of cinema. Its existence is undeniably can be an attraction for a film. In addition to its function to convey the title, typography also has a function as the identity of a film. This identity can certainly represent and reveal the characters behind the film through its visuals. One of the typography in film titles that has a characteristic in each film is Disney animated films. Typography in the title of Disney animated films with the adventure genre certainly has a variety of typography because the adventure genre has many things that happen in the film, from fear, courage, sadness, to joy. Typographic analysis in the title of this film is reviewed based on the Machin's Inventory of Typographical Meaning Potentials method by van Leeuwen through the character approach in the film. With this, designers can create typography for film titles that match the character of the film.